Stagnation-point flow and heat transfer over stretchable plates and cylinders with an oncoming flow: Exact solutions - Turkyilmazoglu, Mustafa (Chemical engineering science, 2021)
•Axial velocities are suppressed by the stretching action of the surfaces.•Pressure depends on both space coordinates and adjusts the flow field.•Temperature field is also damped by the stretching action of the surfaces.•Stretching leads to enhanced heat transfer rates and thus, surface cooling. The stagnation-point of oncoming flow impinging on a stretchable flat plate or a circular cylinder is the subject of the present paper. Exact solutions are targeted for both momentum and thermal fields. Identified analytical solutions are significant as they constitute further exact solutions to the Navier–Stokes and energy equations. These solutions are deduced to be well-known particular solutions in the limiting cases of permeable stationary body surfaces. Findings reveal that stretching has suppressing effect on the axial velocity and temperature distributions. The character of flow impingement is closely adjusted by the relevant physical parameters. Heat transfer rates from the surfaces in both flow geometries are enhanced by the action of walls, with more cooled surfaces in the presence of wall suction.